2018
DOI: 10.26603/ijspt20180389
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the ‘Back in Action’ Test Battery to Standard Hop Tests and Isokinetic Knee Dynamometry in Patients Following Anterior Cruciate Ligament Reconstruction

Abstract: Background: Limb symmetry after anterior cruciate ligament reconstruction may be evaluated using maximal strength and hop tests, which are typically reported using Limb Symmetry Indices (LSIs) which may overestimate function. Purpose:The purpose of this study was to compare the Back in Action (BIA) test battery to standard hop and muscle strength tests used to determine readiness to return to sport (RTS). Study Design: Prospective cohort.Methods: Over two test sessions, 40 ACLR patients were assessed at a mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 34 publications
2
28
0
3
Order By: Relevance
“…Considering the high physical activity level of our sample (pre-injury Tegner 7.4 ± 1.6) and the fact that nearly 50% of patients failed in one or more tests 6 months after surgery, BIA must be considered a very challenging return-to-sports test. Thus, our results confirm an earlier report to demonstrate that BIA is more conservative compared to commonly performed strength and hop tests [21]. The test associated with the greatest failure rate was the single-leg countermovement jump performed with the injured leg, at which 60 out of 245 subjects (24.5%) achieved "poor" or even "very poor" results.…”
Section: Discussionsupporting
confidence: 88%
“…Considering the high physical activity level of our sample (pre-injury Tegner 7.4 ± 1.6) and the fact that nearly 50% of patients failed in one or more tests 6 months after surgery, BIA must be considered a very challenging return-to-sports test. Thus, our results confirm an earlier report to demonstrate that BIA is more conservative compared to commonly performed strength and hop tests [21]. The test associated with the greatest failure rate was the single-leg countermovement jump performed with the injured leg, at which 60 out of 245 subjects (24.5%) achieved "poor" or even "very poor" results.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, a comparison of the BiA test to standard hop tests and isokinetic knee dynamometry in patients after ACL reconstruction showed that the BiA test battery is more physically challenging than the standard hop and isokinetic strength test. There was a significantly greater RTS fail rate compared with standard testing batteries [30]. In order to achieve as distinct data as possible, this test battery seems to be a suitable measurement for evaluating knee function in athletes with a high risk of ACL injury.…”
Section: Discussionmentioning
confidence: 98%
“…The present study explored the utility of smart technology (ViMove) and MatScan pressure sensing mat in assessing coronal plane alignment differences in the assessment of ACL reconstruction patients for return to sport assessment. Accelerometers have been utilised in assessment for return to sport post ACL reconstruction as demonstrated by Gokeler et al , where accelerometers were used to assess jump height and power output asymmetries with hop tests 18 19. We found differences in performance between groups and individuals.…”
Section: Discussionmentioning
confidence: 58%
“…Smart technology has the potential to change the way the clinician interacts with the patient through wearable inertial sensor technologies and influence postoperative recovery 17. It has recently been shown to be beneficial as part of a rehab assessment for ACL patients 18 19. ViMove (DorsaVi, East Melbourne, Australia) is one such device which incorporates the coordinates from an accelerometer and gyroscope into a user-friendly interface displaying lower limb alignment during functional activities.…”
Section: Introductionmentioning
confidence: 99%